2010
DOI: 10.1007/s10658-010-9719-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and spatial distribution of vegetative compatibility types and mating types of Cryphonectria parasitica in the Aydın Mountains, Turkey

Abstract: In this study, the population structure of the chestnut blight fungus Cryphonectria parasitica in the Aydın Mountains was investigated to make inferences about fungal reproduction and population diversity. A total of 213 C. parasitica isolates from eight subpopulations were used to determine vegetative compatibility (vc) and mating types of the population. Furthermore geostatistical analysis was performed to define the spatial structure of the population. The results showed that the isolates were vegetatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…Aydın andİzmir represent almost 40% of chestnut production in Turkey [9]. While the mean production amount per household in Aydın was found to be similar tȯ Izmir in our research, Aydın is reported as the largest producer in Turkey according to total production amount [23,29,34,35].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Aydın andİzmir represent almost 40% of chestnut production in Turkey [9]. While the mean production amount per household in Aydın was found to be similar tȯ Izmir in our research, Aydın is reported as the largest producer in Turkey according to total production amount [23,29,34,35].…”
Section: Discussionsupporting
confidence: 56%
“…The chestnut blight fungus, which has been present in Turkey since the late 1960s, is considered by experts to be the most impactful of these. Most research into chestnut blight mitigation focuses on a biological control known as applied hypovirulence [8,9]. Though shown to be effective, biological control cannot be performed by smallholders.…”
Section: Introductionmentioning
confidence: 99%
“…For the last two decades, chestnut plantations in the region have been under attack by the fungus Cryphonectria parasitica , the cause of a destructive disease known as chestnut blight. Since its first report in the Aegean region in 2001 (Çeliker & Onoğur, ), chestnut blight has caused the death of many chesnut trees especially in areas where the disease has been present the longest (Erincik, Döken, Açıkgöz, & Ertan, ; Erincik, Özdemir, Durdu, Döken, & Açıkgöz, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, the vc‐type diversity of C. parasitica is low (Akıllı, Katırcıoğlu, & Maden, ; Çeliker & Onoğur, ; Erincik et al., , ). EU‐1 is the dominant vc type and is distributed in all regions of Turkey (Gürer, Ottaviani, & Cortesi, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Portugal, northern Spain and southwestern France, the populations are quite different from those in other countries in Europe, and are dominated by vc types EU-11, EU-33, EU-66 and EU-72, which gives evidence for recurring introductions of the pathogen of an origin different from those introduced in Italy ( Robin et al, 2000;Montenegro et al, 2008;Robin et al, 2009) and substantial absence of long-distance spread of the disease. In Greece, southern Italy, Slovakia, the former Yugoslav Republic of Macedonia, Romania and Bulgaria, populations are dominated by the vc type EU-12 (Sotirovski et al, 2004;Perlerou and Diamandis, 2006;Milgroom et al, 2008;Erincik et al, 2011), whereas, in Turkey, vc types EU-12 and EU-1 coexist (Gurer et al, 2001;Akilli et al, 2009). In Georgia, the C. parasitica population has a higher diversity of vc types than those of neighbouring countries, with many new vc types unknown in Europe which have emerged locally through sexual recombination .…”
Section: Intraspecific Diversitymentioning
confidence: 99%